Disfunção burocrática : um estudo de caso do excesso de papel no DAOCS/UFES - Prando, Ana Amélia Fabres (2013)
Taking the Department of Administration of Governing Bodies of Higher Federal University of Espírito Santo (DAOCS / UFES) as a particular case, this study aimed to identify possible excess papers and documents in that Department and its impact on decision-making by the Councils for the University, assisted administratively by aforementioned Department. For this, we used a qualitative approach, with performance of direct observation and semi-structured interviews with employees and Council members. The bureaucracy seeks to make organizations efficient by excellence, based on rationality, neutrality and professionalism, with standardization of behaviors and routines. However, when there is excessive attachment to some characteristics of bureaucracy, we may have dysfunctions or abnormalities. Thus, as a result of extreme attachment to the principle that everything needs to be documented and registered, the consequence will be the excess of paper, including bulky processes, composed of several pages, with transportation difficulties, accommodation, storage and analysis. To think about a reduction in paper consumption has become essential, both in relation to the budget and expenditure of other items such as toner and electricity. At the same time, we can compare to the well fair of employees involved, since paper without proper accommodation, collects dust, representing risk to their health. Added to this, also the desired efficiency of the public service, affected by the exacerbated formalism, leading to delays in the progress of cases